The Selvester QRS score as a predictor of cardiac events in nonischemic dilated cardiomyopathy. Issue 3 (March 2018) - Hiraiwa, Hiroaki; Okumura, Takahiro; Sawamura, Akinori; Sugiura, Yuki; Kondo, Toru; Watanabe, Naoki; Aoki, Soichiro; Ichii, Takeo; Kitagawa, Katsuhide; Kano, Naoaki; Fukaya, Kenji; Furusawa, Kenji; et al.
Highlights: The Selvester QRS score is handily calculated by standard electrocardiography. The QRS score can predict cardiac events in nonischemic dilated cardiomyopathy. The QRS score correlates with the amount of myocardial fibrosis. Abstract: Background: Myocardial fibrosis is associated with poor prognosis in nonischemic dilated cardiomyopathy (NIDCM) patients. The Selvester QRS score on 12-lead electrocardiogram is associated with both the amount of myocardial scar and poor prognosis in myocardial infarction patients. However, its use in NIDCM patients is limited. We investigated the prognostic value of the QRS score and its association with collagen volume fraction (CVF) in NIDCM patients. Methods: We enrolled 91 consecutive NIDCM patients (66 men, 53 ± 13 years) without permanent pacemakers or cardiac resynchronization therapy devices. The Selvester QRS score was calculated by two expert cardiologists at NIDCM diagnosis. All patients were followed up over 4.5 ± 3.2 years. Cardiac events were defined as a composite of cardiac death, hospitalization for worsening heart failure, and lethal arrhythmia. We also evaluated CVF using endomyocardial biopsy samples. Results: At baseline, the left ventricular ejection fraction was 32 ± 9%, plasma brain natriuretic peptide level was 80 [43–237] pg/mL, and mean Selvester QRS score was 4.1 points. Twenty cardiac events were observed (cardiac death, n = 1; hospitalization for worsening heart failure, n = 16; lethal arrhythmia, n = 3). Cox proportional hazard regression analysis revealed that the Selvester QRS score was an independent determinant of cardiac events (hazard ratio, 1.32; 95% confidence interval, 1.05–1.67; p = 0.02). The best cut-off value was determined as 3 points, with 85% sensitivity and 47% specificity (area under the curve, 0.688, p = 0.011). In Kaplan–Meier survival analysis, the QRS score ≥3 group had more cardiac events than the QRS score <3 group (log-rank, p = 0.007). Further, there was a significant positive correlation of Selvester QRS score with CVF ( r = 0.46, p < 0.001). Conclusions: The Selvester QRS score can predict future cardiac events in NIDCM, reflecting myocardial fibrosis assessed by CVF.